Joni Mitchell : new critical readings - Charnock, Ruth (Bloomsbury Academic, 2019)
"Joni Mitchell: New Critical Readings recognizes the importance and innovativeness of the musician and artist Joni Mitchell and the need for a collection that theorizes her work as musician, composer, cultural commentator and antagonist. It showcases pieces by established and early career academics from the fields of popular music and literary studies on subjects such as Mitchell's guitar technique, the politics of aging in her work, and her fractious relationship with feminism. The collection features close readings of specific songs, albums, and performances while also paying keen attention to Mitchell's wider cultural contributions and significance."--